CREATION OF A GEOPORTAL AND ITS ROLE IN OPERATIONAL MONITORING OF THE NATURAL AND MANMADE EMERGENCY CHARACTER IN THE TERRITORY OF THE REPUBLIC OF KAZAKHSTAN - Sh. Zhantayev, Zh.; Nurakynov, S.M.; Gavruk, S.V.; Iskakov, B.A.; Sydyk, N.K.; Merekeyev, A.A. (Academic Scientific Journal of Computer Science, 2020)
This article discusses the space monitoring system, its composition and functional diagram of the basic elements of the system and remote access services to the resources and results of the space monitoring system. The composition of the information support of the system, its formats and sources, and the frequency of updates are described. The basic structure of the geoportal, namely, the subsystem for collecting satellite and ground data, a database, processing and expert interpretation, integration and dissemination of monitoring data, is briefly described. The whole cycle of space monitoring work is described for each priority area, from obtaining raw data to uploading emergency monitoring data to the geoportal in Kazakhstan, including operational data from space monitoring of forest and steppe fires, GPS monitoring of intense movements of the earth’s crust, space monitoring of floods, space monitoring oil pollution of the Caspian Sea with the corresponding "screenshots". The geoportal interface is described.